Respuesta :
What you must do for this case is to solve the system of two equations with two unknowns.
To find the values of x and y.
We have then:
-3x + 9y = 36
4x + 12y = 24
Resolving:
Step 1:
(1/3) * (- 3x + 9y) = (36) * (1/3)
(1/4) * (4x + 12y) = 24 * (1/4)
-x + 3y = 12
x + 3y = 6
Step 2:
6y = 18
y = 18/6
y = 3
Step 3:
-x + 3y = 12
-12 + 3y = x
-12 + 3 (3) = x
x = -3
answer:
x = -3
y = 3
To find the values of x and y.
We have then:
-3x + 9y = 36
4x + 12y = 24
Resolving:
Step 1:
(1/3) * (- 3x + 9y) = (36) * (1/3)
(1/4) * (4x + 12y) = 24 * (1/4)
-x + 3y = 12
x + 3y = 6
Step 2:
6y = 18
y = 18/6
y = 3
Step 3:
-x + 3y = 12
-12 + 3y = x
-12 + 3 (3) = x
x = -3
answer:
x = -3
y = 3
Answer:
(-3,3)
Step-by-step explanation:
Just took the test! Its correct.